1985
DOI: 10.1002/aja.1001740313
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian gamete interactions: What can be gained from observations on living eggs?

Abstract: Studies on fertilization have involved a variety of investigational techniques from the simple to the very complex. Perhaps the most direct approach has been the observation and photographic recording of the interactions of living gametes in vitro. The purpose of this paper is to review the major contributions that have been made, by means of this technique, to our knowledge of mammalian fertilization, and to examine its advantages and limitations. Some of the events of mammalian fertilization that have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Several time-lapse studies [ 30– 32] showed that in a few embryos, fertilization took place several minutes after zona penetration and the sperm wandered in the PVS and/or rotated the oocyte, but such embryos were considered exceptional and their significance was dismissed. Unfortunately, these claims were supported by a very limited number of observations [ 33], and the location of the zona penetration or of the fertilization (i.e., sperm attachment) was not specified, making it difficult to directly compare them with our present results. Although our observation of incongruity between the point of zona penetration and that of fertilization might be explained by the putative spinning of the oocyte, we consider this possibility very unlikely, since only one of 41 embryos (2%) examined in the present time-lapse analysis showed the oocyte spinning more than 90° after sperm attachment.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Several time-lapse studies [ 30– 32] showed that in a few embryos, fertilization took place several minutes after zona penetration and the sperm wandered in the PVS and/or rotated the oocyte, but such embryos were considered exceptional and their significance was dismissed. Unfortunately, these claims were supported by a very limited number of observations [ 33], and the location of the zona penetration or of the fertilization (i.e., sperm attachment) was not specified, making it difficult to directly compare them with our present results. Although our observation of incongruity between the point of zona penetration and that of fertilization might be explained by the putative spinning of the oocyte, we consider this possibility very unlikely, since only one of 41 embryos (2%) examined in the present time-lapse analysis showed the oocyte spinning more than 90° after sperm attachment.…”
Section: Resultsmentioning
confidence: 72%
“…We propose a model in which the space constraints in the oocyte exerted by the ZP and 1pb lead to an increased probability that the swimming sperm localizes and eventually enters into the pb half where more PVS is available. Fertilization is considered to be a two-step process of sperm adhesion and fusion [ 33, 34]. Although CD9 was shown to be required for sperm fusion and to be expressed with no apparent asymmetry on the oocyte surface [ 35, 36], the molecules essential for the sperm adhesion remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple penetrations of the rabbit zona reveal that the angle of penetration trajectory can vary even within one zona, and this path can be almost orthogonal or direct in some muroid rodent eggs mounted beneath a cover glass (Gaddum-Rosse 1985). This makes it seem doubtful that the penetration angle is ordained by some intrinsic characteristic of the zona matrix.…”
Section: Sperm Penetration Of the Zona Pellucidamentioning
confidence: 98%
“…An acrosome-reacted sperm, in the act of passing through the ZP, loses all its acrosomal components, except the equatorial segment and inner acrosomal membrane (Bedford 1970;Moore 1983). After sperm reaches the perivitelline space of the oocyte, the equatorial region of the sperm head fuses with the oolemma and the sperm is gradually engulfed into the ooplasm (Gaddum-Rosse 1985). Sperm fusion with an oocyte awakens the metabolically quiescent oocyte to initiate a series of morphological and biochemical events that lead to oocyte activation and resumption of meiosis (reviewed in Yanagimachi 1994).…”
Section: Fertilizationmentioning
confidence: 99%